Integration of Environmental Sustainability Strategies Within Pre-Construction Processes - Mohammad Affendy, Omardin; Wan Mohd Nazmi, Wan Abdul Rahman; Wan Dagang, Wan Ali (Medwell Journals, 2017)
An awareness of the environmental sustainability in the construction project as it can improve the quality of the work progress. To achieve an environmental sustainability it is important to ensure a project sustainable within green agenda. This study provides an overview of how environmental sustainability concept in practices. A survey has been conducted among construction practitioners in Malaysia focusing on the environmental sustainability concept. The findings suggest that many more efforts could be as to push green construction to the forefront. The contribution of this research, it encourage the environmental awareness to ensure sustainability future. Construction at the managerial level must devise robust and innovative environmental sustainability strategies in order to comply with the sustainability requirements and take advantages of the opportunities arising from the implementation of such practices.